Danza e musica nelle Tavole Iguvine (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
In this paper, we propose a route through a selection of passages from the Iguvine Tables that could be interpreted as music and dance and are connected to some ritual moments. From this analysis it emerges that the action of dancing takes place after a prayer and includes a circular movement at the end of the rite, which could have been accompanied by music or not.
Keywords: Iguvine Tables; rituals; dance; music